Career concerns with exponential learning - Alessandro Bonatti; Johannes Hörner (Theoretical Economics, 2017)
This paper examines the interplay between career concerns and market structure. Ability and effort are complements: effort increases the probability that a skilled agent achieves a one-time breakthrough. Wages are based on assessed ability and on expected output. Effort levels at different times are strategic substitutes and, as a result, the unique equilibrium effort and wage paths are single-peaked with seniority. Moreover, for any wage profile, the agent works too little, too late. Commitment to wages by competing firms mitigates these inefficiencies. In that case, the optimal contract features piecewise constant wages and severance pay.
Keywords: D82; D83; M52; 330; Career concerns; experimentation; career paths; up-or-out; reputation